Upaya Dalam Meningkatkan Kualitas Pengolahan Data Dan Kualitas Informasi - Alfa Nadiah Siregar; Muhammad Irwan Padli Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine efforts to improve the quality of data processing and information quality. The method used is Library Research (Library), in its use this method uses books, and journals both in written form and online. Based on this research, it can be concluded that efforts to improve the quality of data processing and the quality of information have a big impact on life, both for business people, education, health, government, organizations, and society who use it to achieve the goals they want to achieve. Because the resulting impact is very good for facilitating all kinds of activities. Make it easier for people to get accurate information and correct data and make wise decisions. With the increase in the quality of data processing and the quality of information, people are not afraid of making mistakes in getting the information they receive.